Evaluation of left ventricular functions in patients with primary hyperparathyroidism: is there any effect of parathyroidectomy? - KEPEZ, ALPER; MUTLU, BÜLENT; SÜNBÜL, MURAT; YEŞİLDAĞ, OSMAN (SPRINGER WIEN, 2017)
Our aim was to evaluate left ventricular (LV) systolic and diastolic functions of primary hyperparathyroidism (pHPT) patients with detailed echocardiographic analysis and investigate the effect of parathyroidectomy on echocardiographic parameters. A total of 22 eligible consecutive patients with pHPT who underwent parathyroidectomy operation were recruited to the study. Another 22 subjects with similar age, gender and frequency of cardiovascular risk factors compared to patients were used as a control group. Echocardiographic parameters of patients scheduled for parathyroidectomy were compared to healthy matched controls. Echocardiographic parameters measured 6 months after the operation were also compared with preoperative values for each patient. Patients had higher LV mass index compared with controls. There were no significant differences between groups regarding 2D echocardiographic parameters reflecting LV systolic function and tissue Doppler velocities; however, 2D echocardiographic parameters demonstrated impairment in LV diastolic functions compared with controls. Speckle tracking echocardiography (STE) demonstrated similar LV global longitudinal systolic strain; however, left atrial conduit and reservoir functions were significantly reduced in patients with pHPT. In general, there were no significant differences between baseline and postoperative state regarding parameters reflecting LV systolic and diastolic functions; however, STE demonstrated significantly increased LV global longitudinal strain after surgery (22.3 +/- 3.3% vs 20.3 +/- 2.9%, p = 0.026). Patients with pHPT displayed higher LV mass and impairment in LV diastolic function compared with controls. Parathyroidectomy did not lead to significant improvements in LV mass or LV diastolic function; however, subtle but not apparent increases in LV systolic function were observed 6 months after surgery.
Keywords: Hyperparathyroidism; Left ventricular systolic function; Left ventricular diastolic function; Speckle tracking echocardiography; Parathyroidectomy; INTIMA-MEDIA THICKNESS; DIASTOLIC FUNCTION; CAROTID-ARTERY; HORMONE; ECHOCARDIOGRAPHY; DEATH; HEART; MASS